Pentafluoropropionic Acid: An Efficient and Metal-Free Catalyst for the One-Pot Synthesis of Tetrahydrobenzo[b]pyran Derivatives - Naser Montazeri; Taghva Noghani; Mona Ghorchibeigy; Rozita Zoghi (Journal of Chemistry)
Pentafluoropropionic acid (PFPA) efficiently catalyzes the one-pot, three-component reaction of aromatic aldehyde, malononitrile, and dimedone to yield tetrahydrobenzo[b]pyran derivatives in high yields. This method is of great value because of its easy processing, short reaction time, environmentally, and high yields.